IDENTIFICATION STUDY OF SAND CUCUMBER (Holothuria scabra) USING DNA BARCODING IN BUAYA ISLAND ALOR AND SERAYA ISLAND LABUAN BAJO - Gyan Carlo Valentino Yusuf; Marcelien Dj. Ratoe Oedjoe; Nicodemus Dahoklory (Fakultas Perikanan dan Ilmu Kelautan Universitas Borneo Tarakan, 2025)
Holothuria scabra, commonly known as sandfish, is a highly valued sea cucumber species distributed in tropical marine waters, including Indonesia. This study aimed to genetically identify H. scabra populations from Buaya Island (Alor) and Seraya Island (Labuan Bajo) using DNA barcoding of the Cytochrome Oxidase I (COI) gene. The methods included DNA extraction, COI gene amplification via PCR, electrophoresis, sequencing, and phylogenetic analysis. Results showed that all four samples from both locations had 683 bp sequences and 99.12% similarity to the reference H. scabra sequence (NC_027086.1). Phylogenetic analysis grouped all samples into a single clade with a bootstrap value of 100, indicating they belong to the same species. These findings suggest that the H. scabra populations in both locations are genetically monomorphic. This study provides essential scientific data to support sustainable aquaculture and conservation strategies for sandfish in Indonesia